THE DEVELOPMENT OF CHINESE BASIC VOCABULARY MEMORIZATION ABILITY USING GAME-BASED LEARNING OF SECOND-YEAR PRIMARY SCHOOL STUDENTS - Limpradit, Nattawan; Panjiang, Prapas (Journal of MCU Nakhondhat, 2025)
This research aimed to: 1) Compare the Chinese vocabulary memorization abilities of second-year primary school students before and after game-based learning, and 2) Examine their satisfaction with game-based learning in developing fundamental Chinese vocabulary memorization skills. The research is an experimental study. The population consisted of Second-Year Primary School Students in the Thai Muang Subdistrict. The sample group consisted of 28 second-year primary school students from Thai Muang Municipality Kindergarten School (People's Unity), selected through cluster random sampling using the classroom as the sampling unit. The research tools included 1) A lesson plan for developing Chinese vocabulary memorization, 2) A vocabulary memorization assessment, and 3) a satisfaction questionnaire on game-based learning. Data were analyzed using percentage, mean, standard deviation, and dependent t-test for hypothesis testing. The findings revealed that the students' Chinese vocabulary memorization abilities after game-based learning were significantly higher than before at the .01 level. Additionally, the students' satisfaction with game-based learning for improving Chinese vocabulary memorization was at the highest level of satisfaction ( = 4.57, S.D. = 0.12). after the intervention. When considering each aspect, it was found that students were most satisfied with the content, followed by teachers, teaching activities, and teaching media.